Holy Warriors : A Journey into the Heart of Indian Fundamentalism - Fernandes, Edna (London Portobello Books, 2007)
Home to all the major religions, India is also, inevitably, host to virtually every type of religious fanatic. No other nation has witnessed as much proselytization or heard as many war cries in the name of God as India. For centuries, Hindus, Christians, Sikhs, and Muslims have waged bloody wars, sought violent conversion, and declared jihad against their enemies, as their religions have been hijacked by the forces of fundamentalism. Here British-Indian journalist Edna Fernandes travels to the country$1 (Bs recent and past theaters of religious extremism$1 (Bfrom Kashmir to Gujarat, Punjab to Goa$1 (Bto meet the generals and foot soldiers of communal wars who assert their faith in rhetoric and rage. Theirs are stories of bigotry and bloodshed, insecurity and despair, but Fernandes listens with understanding, tolerance, and a deft sense of humor, and paints a uniquely vivid and clear-sighted picture of a country divided by dogma.s
Include Map and Illustrations.
A Journey into the Heart of Indian Fundamentalism.
Keywords: Religious fundamentalism -- India -- Religion